Novice Non-Native English Teachers' Reflections on Their Teacher Education Programmes and Their First Years of Teaching - Sumru Akcan (Universidad Nacional de Colombia, 2016)
This study investigates novice non-native English teachers' opinions about the effectiveness of their teacher education programme and the challenges during their initial years of teaching. The results of a survey administered to fifty-five novice teachers and follow-up interviews identify strengths and weaknesses in their teacher education programme and catalogue the difficulties they faced when they star-ted to teach. The study found significant differences between the content of novice teachers' academic courses in their teacher education programme and the conditions they experienced in classrooms. The major challenges of their first years of teaching were related to lesson delivery, managing behaviour, unmotivated students, and students with learning disabilities. The article includes suggestions to prepare teachers for the actualities of working in schools.